Enhancing mechanical properties of particleboard using waste material (fish bones) - Fatiniziana Shahriman (2024)
This research aims to explore the feasibility and effectiveness of enhancing the mechanical properties of particleboard by incorporating waste material, specifically fish bones, at varying concentrations (5%, 10%, and 15%). The study focuses on evaluating the impact of fish bone fillers on bending strength, tensile strength, and dimensional stability of the particleboard. Employing a detailed methodology that includes preparation of materials from Kelempayan wood and fish bones, along with the use of ureaformaldehyde resin, the research provides valuable insights into the mechanical properties and dimensional stability of the produced particleboard. The findings indicate that the addition of fish bone content improves bending and tensile strengths at a concentration of 10%, but shows a decrease at 15%. The implications of this study are significant in the development of eco-friendly composite materials, utilizing waste as an effective and cost efficient filler alternative in the construction and furniture industries, contributing to waste reduction and sustainable waste utilization. This study also opens avenues for further research in optimizing fish bone content in particleboard to achieve a balance between mechanical strength and environmental sustainability